Ganzheitliche Analyse dreiphasiger enzymatischer Reaktionssysteme mittels kontinuierlicher Flüssig-Flüssig-Phasentrennung [Holistic analysis of three-phasic enzymatic reaction systems using continuous liquid-liquid phase separation] - Zitzewitz, Philip; Fieg, Georg (Chemie Ingenieur Technik, 2015)
The enzymatic hydrolysis of methyl octanoate via immobilized Candida antarctica lipase B was studied as an exemplary reference system from the field of enzymatically catalyzed liquid-liquid-solid systems. The experimental investigation of this system was performed in an innovative recycle packed-bed reactor with continuous liquid-liquid phase separation. This setup allows for both a biphasic as well as a singular phase reactor feed. For the first time, a holistic experimental investigation of both operation modes at various operating conditions was conducted. In addition to the presentation of the experimental results, the basics of the mathematical modeling are shown and a model validation is performed.